POPULASI DAN HABITAT Nepenthes ampullaria Jack. DI CAGAR ALAM MANDOR, KALIMANTAN BARAT - ., Maysarah; Zuhud, Ervizal A.M.; Hikmat, Agus (Media Konservasi, 2017)
Nepenthes ampullaria Jack. is a species which adapted on the nutrient-poor areas in Mandor nature reserve.  Its could be increasing the quality of Mandor nature reserve as protected area. This research aims to study the population and habitat of N. ampullaria in the Mandor nature reserve. This study was conducted at two habitats, heath forest and peat swamp forest. Observations were made on, population abundance and habitat factors of  N. ampullaria. The results showed that the highest population density of N. ampullaria was in heath forest. Their are growth in groups. Vegetation analysis showed that constituent species habitat of N. ampullaria consist of 69 species from 39 familly. Result of identification to insects showed Formicidae is dominant family that trapped in pitcher of N. ampullaria. Temperature and humidity in N. ampullaria’s habitat has been switable for requirements growth of pitcher plant. Rainfall during the study was normally. Ratio of sand and soil on both affected the improvement of individual N. ampullaria in Mandor nature reserve. Keywords: habitat, Mandor nature reserve, Nepenthes ampullaria Jack, population